Determination of water requirements for major Crops in Sindh using Cropwat model - Ateeque Rehman; Ashfaque Ahmed Memon; Shafi Muhammad Kori (Penerbit Universiti Kebangsaan Malaysia, 2023)
Due to population growth and increasing urbanization trends, there is a shortage of water around the world. Irrigation systems are critical for increasing crop output and ensuring food security. Desertification caused by humans and water shortages have further exacerbated the world’s regular water scarcity, putting a significant impact on food production. Water scarcity and rising food demands necessitate greater efficiency in water use, both in rain-fed and irrigated agriculture. Hence, it is the most demanding requirement for the farming community to use some type of irrigation planning to conserve the limited water resources. The purpose of this study is to calculate crop water requirements and irrigation scheduling for some major crops in Sindh using the CROPWAT model developed by FAO of United Nations. In this regard, selection from among the major crops cultivated in the Sindh province of Pakistan was made in such a way at least one crop from each category be included in this research. Accordingly, Wheat as Rabi, Rice as Kharif, Sugarcane as Perineal and Chili and Rape-seed Mustard as Cash Crops were selected. CROPWAT model calculates crop water requirements and irrigation scheduling from existing or new climatic- and crop-information. The Input crop data for CROPWAT software was obtained from various online resources and published information, whereas, climatic data incorporated in the CLIMWAT tool attached with CROPWAT was utilized. In addition, the software used average rainfall data of the particular years for each crop observed at DRIP Tandojam metrological station. The results of water requirements for the crops were obtained through CROPWAT model are: Wheat (352.1 mm); Rice (1662.5 mm); Sugarcane (2184.5 mm); Chili (714.4 mm); and Rape-seed Mustard (475.6 mm), while those by lysimeter were: Wheat (415 mm); Rice (1633 mm); Sugarcane 2150 mm); Chili (808.9 mm); and Rape-seed mustard (424.87 mm). These results delineate that there is decrease in crop water requirement of Wheat, Rice, Sugarcane and Chili to the tune of 15%, 1.5%, 11.6% and 1.7%, respectively, whereas an increase of 12% for Rape-seed mustard.